Joint audit as a tool to improve the quality of financial report: Field study: (environment of professional practice in the Arab Republic of Egypt) - Ismail, Salwa Hussein Roshdy (Journal of Economic, Administrative and Legal Sciences, 2021)
This research aims to clarify the role of the joint review in improving the quality of financial reports. In the completion of this research, the researcher relied on the analytical descriptive approach and relied on the Statistical Package for Social Science Spss / Pc + in testing hypotheses, analyzing the sample and discharging data. Classifying and analyzing them. The research concluded that there is a positive relationship between the application of the joint audit and the increase in the quality of the audit process, and the existence of a positive relationship between the joint audit and the quality of financial reports. The research recommended the necessity of obliging the major offices to cooperate with each other to develop methods of professional practices such as the joint audit method and to clarify its importance and advantages.